Germinação e armazenabilidade de sementes de pequizeiro - Diemesson San Tiago Mendes (2015)
The pequizeiro is an important native fruit tree in the Brazilian cerrado, being widely used in the regional cuisine and with a great potential in the pharmaceutical and cosmetic industry. Its operation is limited by the difficulty in obtaining seedlings, restricting the cash crops deployment and the domestication studies. The obstacle in this species seedlings production is related to their seeds dormancy, as well as other factors such as the extraction form, the seed quality and longevity, and the seeding place. Thus, the objectives were to develop a safe method of seed extraction, to know the pyrenes longevity and germination after storage and planting, and to quantify the lipid peroxidation and the seeds deterioration. We evaluated the isolated seed efficiency in the pequizeiro extraction method, using the manual lathe, emery, modified pliers and tweezers. In seeds and pyrenes, stored and sown under controlled conditions (BOD and greenhouse) and natural, it was determined the lipid peroxidation (malondialdehyde - MDA) indicator concentration, the seeds germination, vigor and deterioration . The equipment use mentioned above provided the pequi seeds efficient extraction. After 40 days of the pyrenes storage, the isolated seeds (cored) outweigh the numbness and have high germination. On the other hand, the storage time increase leads to the seeds deterioration, found by both the high mortality rate and the increase in lipid peroxidation. In natural conditions the pyrenes emergency rate does not exceed 5% and is restricted to the period of greatest rainfall, while in controlled conditions this rate is about 30% with almost all the emergency occurring in the first four months.